2002
DOI: 10.1046/j.1365-2982.2002.00330.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cholecystectomy on duodenojejunal motility in humans

Abstract: We hypothesized that certain gastrointestinal symptoms following cholecystectomy could be explained by motor disturbances. To test this hypothesis, we compared pre- and post-operative motor patterns between symptomatic and asymptomatic patients after surgery to evaluate whether some motor changes could be induced by gallbladder removal and associated with symptoms. Twenty-three patients were prospectively evaluated before and 3 months after cholecystectomy. After surgery, 17 patients were asymptomatic and six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2011
2011

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Prevention of gallbladder bile flow into the duodenum via cholecystectomy or atropine administration resulted in the failure of xenin‐induced jejunal response. In a previous study, it was reported that cholecystectomy did not markedly modify the duodenojejunal motor status 13 . After cholecystectomy, normal spontaneous IMCs were observed in all cases.…”
Section: Discussionmentioning
confidence: 56%
“…Prevention of gallbladder bile flow into the duodenum via cholecystectomy or atropine administration resulted in the failure of xenin‐induced jejunal response. In a previous study, it was reported that cholecystectomy did not markedly modify the duodenojejunal motor status 13 . After cholecystectomy, normal spontaneous IMCs were observed in all cases.…”
Section: Discussionmentioning
confidence: 56%
“…Some authors have implicated local inflammation in the duodenojejunal region as a contributing factor in the pathomechanism of intestinal paresis [1,19,20]. In our department, patients undergoing laparoscopic cholecystectomy are spared the placement of an intraperitoneal drain, or when one is placed, it remains in place for significantly shorter time than in patients undergoing open cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are in accordance with these of Le Blanc‐Louvry et al . who evaluated, in a prospective study, patients with cholelithiasis preoperatively and postoperatively, with duodenojejunal manometry 9 . In that study it was also shown that removal of the gallbladder has a limited effect on duodenojejunal motility.…”
Section: Discussionmentioning
confidence: 99%